2018
DOI: 10.1016/j.diagmicrobio.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a multiplex PCR point-of-care test for influenza A/B and respiratory syncytial virus on an acute pediatric hospital ward

Abstract: Patients with respiratory infections are often managed presumptively until confirmation of infection status. We assessed the impact of introducing the Enigma® MiniLab™ FluAB-RSV point-of-care test (POCT) on patients admitted with a suspected respiratory virus driven illness in an acute pediatric ward. This utilized a before and after design (respiratory viral seasons 2013/14 versus 2014/15). Following POCT implementation, oseltamivir prescribing increased in patients with influenza (OR = 12.7, P = 0.05, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
6
10
2
Order By: Relevance
“…In agreement with prior studies [20][21], we found that prescription of neuraminidase inhibitors (NAI) increased post-introduction of an influenza POCT (Table II). Whilst no randomized control trials (RCTs) have examined the effectiveness of NAI in inpatients, a large meta-analysis of cohort data from the H1N1 pandemic suggested that NAI use within 48H of symptoms may reduce mortality by as much as 50% -adjusted odds ratio (aOR) 0.50 (95% CI, 0.37-0.67%, p< 0.0001) [22].…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with prior studies [20][21], we found that prescription of neuraminidase inhibitors (NAI) increased post-introduction of an influenza POCT (Table II). Whilst no randomized control trials (RCTs) have examined the effectiveness of NAI in inpatients, a large meta-analysis of cohort data from the H1N1 pandemic suggested that NAI use within 48H of symptoms may reduce mortality by as much as 50% -adjusted odds ratio (aOR) 0.50 (95% CI, 0.37-0.67%, p< 0.0001) [22].…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…A Spanish study analyzing data across 6 influenza seasons also found NAI had greatest impact if given within 48H, but benefit for administration up to five days post symptoms onset was observed [23]. ED influenza POCT may have increased antiviral prescriptions for those with confirmed influenza by enabling diagnosis within 48H of symptom onset [20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In agreement with prior studies, we found that prescription of oseltamivir increased post-introduction of an influenza virus POCT (data not shown) [19–21]. Oseltamivir treatment is recommended by UK Public Health England for all patients hospitalised with influenza [22].…”
Section: Discussionsupporting
confidence: 91%
“…Inpatient settings. Similarly, observational case-control studies of inpatients demonstrated that positive rapid respiratory virus testing was associated with less antibiotic use in both pediatric (7375) and adult (76) study populations, as well as increased appropriate antiviral use in pediatric and adult populations, compared to patients with negative test results (7577). When respiratory virus diagnosis via DFA testing was available within 24 h, significant reductions in the duration of hospitalization and antibiotic therapy, as well as the number of microbiological investigations, were observed (78).…”
Section: Cost-effectiveness Of Rapid Testingmentioning
confidence: 99%